2019
DOI: 10.1177/2325967118823712
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Clinical Outcomes After Proximal Hamstring Repair

Abstract: Background:Proximal hamstring avulsions cause considerable morbidity. Operative repair results in improved pain, function, and patient satisfaction; however, outcomes remain variable.Purpose:To evaluate the predictors of clinical outcomes after proximal hamstring repair.Study Design:Case series; Level of evidence, 4.Methods:We retrospectively reviewed proximal hamstring avulsions repaired between January 2014 and June 2017 with at least 1-year follow-up. Independent variables included patient demographics, med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…Patients with complete proximal hamstring tears demonstrated significantly higher mHHS post-operatively compared to partial proximal hamstring tears, corroborating with Barnett et al's data on open repairs [28]. Bowman et al [34] analyzed a sub-cohort of 10 patients treated endoscopically, among an overall cohort of 58 patients treated with open and endoscopic techniques. Authors explained that the study was not adequately powered to detect any meaningful differences between the open and endoscopic sub-cohorts; however, the endoscopic cohort did well in terms of satisfaction, pain, complication rates, and patient-reported functional outcomes.…”
Section: Endoscopic Repairsupporting
confidence: 62%
“…Patients with complete proximal hamstring tears demonstrated significantly higher mHHS post-operatively compared to partial proximal hamstring tears, corroborating with Barnett et al's data on open repairs [28]. Bowman et al [34] analyzed a sub-cohort of 10 patients treated endoscopically, among an overall cohort of 58 patients treated with open and endoscopic techniques. Authors explained that the study was not adequately powered to detect any meaningful differences between the open and endoscopic sub-cohorts; however, the endoscopic cohort did well in terms of satisfaction, pain, complication rates, and patient-reported functional outcomes.…”
Section: Endoscopic Repairsupporting
confidence: 62%
“…One article by Shambaugh et al 34 discussed operative and nonoperative management of proximal hamstring repair; however, only data from patients treated operatively were included in analysis. Quality assessment of studies per the MINORS criteria demonstrated a mean score of 12.9 (range, [11][12][13][14][15]. Given the nature of the clinical research, all included studies had a reduced quality assessment score owing to a lack of control groups, patient groups representative of the general population, and in-depth statistical analysis of data, making their ideal score 16.…”
Section: Resultsmentioning
confidence: 99%
“…Most of their patients presented within the acute phase (<4 weeks after symptom onset), with minimal complications noted. Furthermore, Bowman et al 4 showed comparable results between open and endoscopic repair of proximal hamstring tendon tears. Kayani et al 20 reported their results with surgical management of chronic partial proximal hamstring tendon tears in a case series that included 41 patients.…”
Section: Discussionmentioning
confidence: 94%